Household Labor Supply and Welfare Participation in Sweden - Lennart Flood; Jörgen Hansen; Roger Wahlberg (Institute for the Study of Labor (IZA), 2003)
In this paper, we formulate and estimate a structural, static model of household labor supply and multiple welfare program participation. Given the complicated nature of both the income tax schedule and the benefit rules for different welfare programs, we use unique access to a very detailed micro-simulation model to generate accurate budget sets for each work-welfare combination. Moreover, when determining the budget sets, we use extraordinary high-quality data on earnings and other types of incomes, obtained both from employers and from income tax records. The results suggest that labor supply among two-parent families in Sweden is quite inelastic. A policy simulation designed to increase labor supply incentives for low income families generated substantial positive welfare effects, despite only minor increases in labor supply and decreases in welfare participation.
Keywords: J2; 330; household labor supply; welfare; unobserved heterogeneity; Arbeitsangebot; Steuerprogression; Sozialhilfe; Schweden